Electret mechanism, hysteresis, and ambient performance of sol-gel silica gate dielectrics in pentacene field-effect transistors - Cahyadi, Tommy (2012)
The electret induced hysteresis was studied in sol-gel silica films that result in higher drain currents and improved device performance in pentacene field-effect transistors. Vacuum and ambient